Does PD-L1 Positivity in Inflammatory Cells Correlate with PD-L1 Expression in Tumor Cells in Colorectal Adenocarcinoma?. (28th October 2020) - Broadwater, D R; Williams, G; Messersmith, L; Brady, R
Abstract: Introduction/Objective: Drugs targeting the programmed death-1 (PD-1) and programmed death-ligand 1 (PD-L1) checkpoint is an important type of novel immunotherapy. These checkpoint inhibitors are being used in a wide variety of cancers, including colorectal carcinoma (CRC). PD-L1 expression on tumor cells in CRC is predictive of good response to checkpoint inhibitor therapies. PD-L1 expression on tumor infiltrating immune cells (TIIC) is increasingly observed and independently portends good prognosis. The relationship between PD-L1 positivity in TIIC and tumor cells is not well established. In this study, the relationship and correlation of PD-L1 positivity in TIIC and tumor cells were retrospectively reviewed. Methods: 197 sections of CRC from 33 cases (mean of 6 sections/case) with heterogeneous expression of PD-L1 on tumor cells were stained for PD-L1 with immunohistochemistry. None of the patients had received neo-adjuvant therapy. The presence of tumor cells and immune cells with positive PD-L1 expression was noted for each section. Results: Immune cells were positive in 79% of the sections examined. TIIC were positive in 56% of the sections examined. A Cohen's correlation study showed correlation between tumor cells and TIIC in 77% of the cases (k=0.51, moderate agreement). There was at least one section with PD-L1 positive TIIC in 97% of cases. Conclusion: This study shows that PD-L1 is expressed in TIIC in the vast majority of CRC cases designated PD-L1 positive and that PD-L1 is positive in TIIC at a higher rate than in tumor cells. The moderate correlation is interesting, perhaps suggesting that if TIIC are noted to be positive for PD-L1 and tumor cells are not, additional sections of tumor should be stained.